2015
DOI: 10.1111/jar.12204
|View full text |Cite
|
Sign up to set email alerts
|

Support Needs of Fathers of Children with ASD: Individual, Family, Community and Ideological Influences

Abstract: Fathers are resourceful parents who compel a critical re-examination towards advances in father-friendly practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 43 publications
2
29
0
4
Order By: Relevance
“…The high levels of paternal engagement reported here echo those discussed by Shave & Lashewicz, (2015) in research exploring the support needs of fathers of children with autism and those discussed by Towers (2009). In both studies, men undertook a wide range of responsibilities for their children, often within the constraints of full-time employment, as was the case here.…”
Section: Discussionsupporting
confidence: 67%
“…The high levels of paternal engagement reported here echo those discussed by Shave & Lashewicz, (2015) in research exploring the support needs of fathers of children with autism and those discussed by Towers (2009). In both studies, men undertook a wide range of responsibilities for their children, often within the constraints of full-time employment, as was the case here.…”
Section: Discussionsupporting
confidence: 67%
“…() showed that fathers chose to reduce their working hours and refrain from promotional opportunities, which concurs with the findings of this study. Several studies have mentioned the need of a flexible workplace (Carpenter and Towers ; Crowell and Leeper ; Golden ; Shave and Lashewicz ; Venter ) and the choice of self‐employment to provide flexibility for the ‘unplanned demands of caring’ (Wright et al . ), which highlight the need for flexibility at companies and organisations to support their employees with children with disabilities.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Overall, families with children with disabilities experience more difficulties compared with families with typically developing children (Pelchat et al . ; Shave and Lashewicz ). However, the impact of having a child with a disability varies between families, as some families ‘flourish in the presence of disability, while others do not’ (Faragher and Van Ommen , p. 42).…”
Section: Introductionmentioning
confidence: 99%
“…While much of the international research of children with intellectual disabilities captures parents experiences (Behrani & Shah, ; Hastings & Taunt, ; Pisula & Porębowicz‐DoÈrsmann, ), the research primarily relies on mothers voices (Chandravanshi et al., ; Mathew & Nair, ; Rajan, Romante, & Srikrishna, ). However, as fathers are now recognised as equal partners in their child’s care, the body of research interest is growing internationally (Al‐Yagon, ; Carpenter & Towers, ; Cohen, Zeedyk, Tipton, Rodas, & Blacher, ; Kumar & Joshi, ; Paynter, Davies, & Beamish, ; Shave & Lashewicz, ; Takataya et al., ; Towers ).…”
Section: Introductionmentioning
confidence: 99%
“…. However, as fathers are now recognised as equal partners in their child's care, the body of research interest is growing internationally (Al-Yagon, 2015;Carpenter & Towers, 2008;Cohen, Zeedyk, Tipton, Rodas, & Blacher, 2016;Kumar & Joshi, 2015;Paynter, Davies, & Beamish, 2018;Shave & Lashewicz, 2016;Takataya et al, 2016;Towers 2009).…”
mentioning
confidence: 99%